Will FinTech make regional banks superfluous for small firm finance? Observations from soft information‐based lending in Germany. (10th December 2019) - Flögel, Franz; Beckamp, Marius
Abstract: Regional banks have a competitive advantage in that short distances to clients enable the use of soft information for superior lending decisions. If the ambition of FinTech start‐ups to create superior screening and monitoring technologies materialises, this advantage would be diminished and regional banks would become superfluous for small firm finance. To explore this claim, the paper in hand analyses qualitative empirical data about the lending processes and rating system use of regional German savings banks. In essence, the results from participant observation and interviews clarify the importance of "real" soft information for critical lending decisions. The context specificity and limited verifiability of "real" soft information hamper it from being hardened through the use of rating systems and other bank‐ICT. Though FinTech's scoring technologies may overcome the first limitation, it appears likely that in the course of scoring development "real" soft information will be systematically crowded out due to the manipulation problem. The paper expects improved access to finance for SMEs if FinTech solutions overcome both limitations of "real" soft information use, or if peer‐to‐peer lending and regional banks coexist. Deteriorated access to finance is expected if FinTech companies displace the relationship banking of regional banks due to enhanced competition, without preserving the advantages of "real" soft information with superior screening and monitoring technologies. The paper concludes with recommendations on how to prevent deteriorated access to finance for small firms by promoting fair competition and FinTech innovations.